2009
DOI: 10.1007/s12016-009-8186-2
|View full text |Cite
|
Sign up to set email alerts
|

Atopy Risk in Infants and Children in Relation to Early Exposure to Fish, Oily Fish, or Long-Chain Omega-3 Fatty Acids: A Systematic Review

Abstract: There are two main families of polyunsaturated fatty acids (PUFAs), the n-6 and the n-3 families. It has been suggested that there is a causal relationship between n-6 PUFA intake and allergic disease, and there are biologically plausible mechanisms, involving eicosanoid mediators of the n-6 PUFA arachidonic acid, that could explain this. Fish and fish oils are sources of long-chain n-3 PUFAs and these fatty acids act to oppose the actions of n-6 PUFAs. Thus, it is considered that n-3 PUFAs will protect agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
131
1
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 165 publications
(140 citation statements)
references
References 73 publications
(359 reference statements)
1
131
1
7
Order By: Relevance
“…The study aimed specifically at validating the intake of n-3 FAs, as these have a potential role in asthma and allergic diseases (Kremmyda et al, 2009). We found a good level of repeatability in the FFQ, although we found evidence that intakes from FFQ t1 were systematically and significantly higher than intakes from FFQ t2 in most centres and in the total sample.…”
Section: Discussionmentioning
confidence: 99%
“…The study aimed specifically at validating the intake of n-3 FAs, as these have a potential role in asthma and allergic diseases (Kremmyda et al, 2009). We found a good level of repeatability in the FFQ, although we found evidence that intakes from FFQ t1 were systematically and significantly higher than intakes from FFQ t2 in most centres and in the total sample.…”
Section: Discussionmentioning
confidence: 99%
“…It is now considered that supply of EPA and DHA to the fetus might be important in promoting appropriate immune development 117,118 . With regard to the latter, there is some evidence that early fish and LC n-3 PUFA exposure protects against immune dysfunctions like sensitisation to allergens (atopy), allergy and asthma in infancy and childhood 119 . Epidemiological studies looking at the effect of maternal fish consumption during pregnancy and fish consumption during infancy/childhood suggest that fish consumption may play a protective role against atopic disease development in children.…”
Section: B Fatty Acids In Utero: Fetal Growth and Developmentmentioning
confidence: 99%
“…GOKSÖ R et al [138] confirmed that the protective effect of early (before 9 months of life) fish introduction into an infant's diet against wheezing in early childhood is also present for atopic asthma at school age. A recent systematic review, however, concluded that the evidence is inconsistent from the epidemiological studies investigating the effects of fish intake during infancy and childhood on atopic outcomes in infants or children, and that further studies are needed [139]. Finally, in the context of the PASTURE (Protection against Allergies Study in Rural Environments) birth cohort study conducted in five European countries, RODUIT et al [140] showed that an increased diversity of foods introduced in the first year of life had a significant protective effect against the later development of asthma, food allergy and food sensitisation, and that reduced food diversity was associated with reduced expression of Foxp3.…”
Section: Paediatric Respiratory Epidemiologymentioning
confidence: 99%